Thermal Simulation of Custom Designed House to Test Application of new Cooling methods - Kharrufa, Sahar Naieeb; Ebraheem, Yahya Adel; Jasirn, Nagham Ahmad (Iraqi Journal of Architecture and Planning, 2018)